Berdiferensiasi konten, proses, dan produk: studi pembelajaran berdiferensiasi untuk mengembangkan numerasi di SDN Sapit - Nurmawanti, Iva; Indraswati, Dyah; Fauzi, Asri; Amrullah, Lalu Wira Zain; Putra, Gita Prima (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2023)
Numeracy is a skill needed in the 21st century. Numeracy skills are also the focus of the Independent Curriculum. One thing that can be used as an alternative for developing student numeracy is differentiated learning. In differentiated learning, there is differentiation of content, process, and product models. Therefore, this research aims to determine the differentiation of content, processes, and products oriented toward developing numeracy skills at SDN 1 Sapit, West Lombok. This research approach is qualitative with a phenomenological type. This research also involved one grade 1 teacher and six students as subjects. Data was collected through observation and interviews. The results of this research indicate that differences in students' ability levels determine differences in content, processes, and products in the learning process. Apart from that, the differences in methods also determine the guidance teachers can provide to facilitate students' diverse abilities.